Sustainable development goals: Leveraging the global agenda for driving health policy reforms and achieving universal health coverage in India - Rajeev Gera; Rajesh Narwal; Manish Jain; Gunjan Taneja; Sachin Gupta (Wolters Kluwer Medknow Publications, 2018)
Universal Health Coverage (UHC) is now the critical yardstick for countries to measure and track progress toward the "Sustainable Development Goals (SDGs)." Being a signatory, India has started taking measures to attain the targets laid out within the SDG framework and achieving the UHC. With India's National Health Policy (NHP) - 2017 in place, the policy environment for transforming country's health landscape coincides with that of the global approach toward strengthening of health systems and achieving UHC. It is imperative that for achieving the desired outcomes laid down in the SDGs and NHP-2017, coordinated actions are required including political action for making health an individual's right; effective stewardship from the National Ministry of Health and Family Welfare; reorganization of health-care service delivery implementing a "systems approach;" ensuring financial protection against health-care costs; and enhancing community participation and accountability. Undertaking these steps, imbibing the learning, and dwelling upon global experiences can help the country strongly move forward towards achieving global and national targets, thereby ensuring UHC for all its citizens.